A study on the effects of carbon to nitrogen layers in semi passive aerated reactor for organic waste decomposition - Kamaruddin M.A.; Idrus A.F.M.; Norashiddin F.A.; Zawawi M.H.; Alrozi R. (American Institute of Physics Inc., 2023)
The decomposition of green waste and brown waste in relative proportions of 1:1, 2:1 and 3:1 was studied in three successive experiments conducted at Desasiswa Bakti Permai, Universiti Sains Malaysia, Penang. The research involved the determination of the quality of compost produced from the different mixture ratio of green waste and brown waste. Three different 200L capacity reactor that made of 4mm thick poly vinyl chloride (PVC) was used as a Semi Passive Aerated Reactor. Temperature and pH were controlled over 89 days (three months) of composting process. Moisture Content, Calorific Value, C:N ratio and Germination Index of the compost product were analyzed. The final moisture content were 23%, 32% and 54% while the final C:N ratio were 23,21 and 14 respectively. The recommended mixture ratio for composting are in relative proportions 3:1 with final C/N ratio of 14 with Moisture content of 52% and 75% germinated seeds. 2018 Author(s).